From Backpain to Paraplegia: A Rare Primary Presentation of Metastatic Ovarian Cancer in Pregnancy - Çayan, Filiz; Doruk, Arzu; Köseoğlu, Aslı; Alımlı, Mutlu; Cinel, Leyla; Dilek, Saffet (Gynecology Obstetrics & Reproductive Medicine, 2011)
Vertebral metastasis from epithelial ovarian carcinoma is extremely rare and usually diagnosed at autopsy. We present here an unusual case of pregnant woman who developed paraplegy, due to thoracal vertebral metastasis and pathologic vertebral fracture of ovarian carcinoma.